ANALISIS TINGKAT AKURASI MODEL PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK DI BURSA EFEK INDONESIA - Shauma Zahwa Azzahra (2022)
This study aimed at determining whether there are differences in the results of financial distress predictions when calculated using the modified Altman Z-Score model, the Springate model, and the Zmijewski model. This research was also conducted to find out which model has the highest level of accuracy. The population in this study are companies in the transportation and logistics sector on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sample in this study was selected using the purposive sampling technique and obtained as many as 15 companies. The data in this study were processed using parametric statistical tests with paired sample t-test and the accuracy test. The results conclude that there is a significant difference in results between the Springate and Zmijewski models in predicting financial distress and the model that has the highest level of accuracy is the Springate model with a value of 70,77%, followed by the Zmijewski model of 67,69% and the Altman model of 50,29 %.